Dynamics of soil organic carbon mineralization and C fractions in paddy soil on application of rice husk biochar. (August 2018) - Munda, Sushmita; Bhaduri, Debarati; Mohanty, Sangita; Chatterjee, Dibyendu; Tripathi, Rahul; Shahid, M.; Kumar, Upendra; Bhattacharyya, P.; Kumar, Anjani; Adak, Totan; Jangde, Hemant K.; Nayak, A.K.
Abstract: Biochar plays a pivotal role in carbon storage-fractionation-mineralization process in soil. However, uncertainty still remains about the influence of biochar on these inter-related processes that links to C cycling in soil. A three years field experiment was initiated in 2013 at ICAR-National Rice Research Institute, Cuttack, India, to study the deviation in C mineralization and C fractions caused by the application of six doses of rice husk derived biochar (RHB), ranging from 0.5 t ha −1 to 10.0 t ha −1 . The results showed an increase in cumulative CO2 -C emission with increasing RHB rates. However, the model-fitted mineralization rates (dC/dt) did not show significant difference between treated and control soils at the end of incubation period in a laboratory study. In addition, microbial quotient and % C from RHB utilized showed a decreasing trend with increasing rates of RHB application, establishing the carbon sequestration potential of RHB. The highest rate (10.0 t ha −1 ) of RHB application accumulated maximum total organic C (3.26%) and a larger share of non-labile C (63.8%) among the treatments. An increase in rice grain yield (1–24%, depending on rate of RHB application) was observed with increasing rates of RHB which further established that RHB application not only enhanced C storage but also enhanced the productivity of rice by enhancing the soil fertility. Highlights: Field evaluation of role of rice husk biochar on C sequestration. The relationship between active and passive pool of soil C with C mineralization under biochar application was envisaged. Rice husk biochar application improved soil fertility and increased rice grain yield. Lability index of C and microbial quotient decreased with increasing rate of biochar application. Rice husk biochar has a definite role towards C sequestration.